2017
DOI: 10.2147/ijn.s124119
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular melatonin efficiently downregulates sodium fluoride-induced rat hepato- and broncho- TNF-α, TGF-β expressions, and associated oxidative injury: a comparative study of liposomal and nanoencapsulated forms

Abstract: The importance of fluoride as a natural and industrial toxicant is recognized worldwide. We evaluated the regulating role and biological effect of vesicular (liposomal and nanoencapsulated) melatonin (N-acetyl-5-methoxytryptamine) for drug delivery and controlled release on the depletion of inflammatory mediators, as well as oxidative damage in sodium fluoride (NaF)-treated lungs and liver. Hepatic and bronchial damage was induced in Swiss albino rats with a single acute ingestion of NaF (48 mg/kg body weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…From the image, it is revealed that the morphology of the formulation changed, evidencing the successful conjugation of BSA with Q-LNs. The SEM image BSA conjugated Q-loaded LNs is validated using reported image of surface-modified LNs (Mishra et al 2019) and (Sana et al 2017).…”
Section: Sem Analysismentioning
confidence: 88%
“…From the image, it is revealed that the morphology of the formulation changed, evidencing the successful conjugation of BSA with Q-LNs. The SEM image BSA conjugated Q-loaded LNs is validated using reported image of surface-modified LNs (Mishra et al 2019) and (Sana et al 2017).…”
Section: Sem Analysismentioning
confidence: 88%
“…proteins such as siderophores cannot differentiate Ga from Fe , and thus, the growth of the pathogens becomes inhibited by Ga through the blockage of the iron dependent pathways.However, free gallium compounds such as gallium-maltolates, nitrates, chlorides, oxides, nitrides and oxynitrides would be more effective approach for the treatment of infections if these particles become nanosized in a regulated synthesized manner and surface-functionalized with bioactive molecules such as sugars, proteins, peptides, genes, ligands and encapsulated within vesicular systems for their targeting to specic site of interest [4,28]. This review illustrates especially the biological efcacies of GaNPs for the treatments of infective organisms and cancer to consider as a probable effective delivery system.…”
Section: +mentioning
confidence: 99%
“…Few investigators prepared GaNPs and GaNPs-loaded glucan particles for the delivery of gallium and inhibitions of hypercalcemic malignancy and HIV-infected macrophages [25,43]. As GaNPs lack specicity to the cells, their loading or encapsulation with carriers may result in efcient targeted delivery to macrophages by the receptor-mediated active or passive uptakes mechanisms [43,4,28].…”
Section: Gallium Nanoparticles As Delivery Systemmentioning
confidence: 99%
“…The release kinetics of melatonin shows slow-release features in early digestive stages and more through characteristics in later stages of simulated gastric fluids [21]. Furthermore, vesicular (liposomal and nanoencapsulated) forms of melatonin efficiently downregulate sodium fluoride-induced rat hepato-and broncho-TNF-α, TGF-β expressions, and associated oxidative injury, as well as oxidative damage in sodium fluoride (NaF)-treated lungs and liver [22]. The nanoencapsulated melatonin was evaluated as a more powerful remedial therapy in comparison with liposomes, in terms of its efficacy in regulating NaF-intoxicated oxidative injury [22].…”
Section: Liposomes and Lipid Drug Delivery Nanosystemsmentioning
confidence: 99%
“…Furthermore, vesicular (liposomal and nanoencapsulated) forms of melatonin efficiently downregulate sodium fluoride-induced rat hepato-and broncho-TNF-α, TGF-β expressions, and associated oxidative injury, as well as oxidative damage in sodium fluoride (NaF)-treated lungs and liver [22]. The nanoencapsulated melatonin was evaluated as a more powerful remedial therapy in comparison with liposomes, in terms of its efficacy in regulating NaF-intoxicated oxidative injury [22]. Melatonin also encapsulated into liposomes produced using supercritical carbon dioxide (an easier technique compared to thin-film hydration method) [23].…”
Section: Liposomes and Lipid Drug Delivery Nanosystemsmentioning
confidence: 99%